Recent Advances in Signal Amplification to Improve Electrochemical Biosensing for Infectious Diseases - Zhou, Xingcheng; Schuh, Daena A.; Castle, Lauren M.; Furst, Ariel L. (Frontiers in Chemistry, 2022)
The field of infectious disease diagnostics is burdened by inequality in access to healthcare resources. In particular, “point-of-care” (POC) diagnostics that can be utilized in non-laboratory, sub-optimal environments are appealing for disease control with limited resources. Electrochemical biosensors, which combine biorecognition elements with electrochemical readout to enable sensitive and specific sensing using inexpensive, simple equipment, are a major area of research for the development of POC diagnostics. To improve the limit of detection (LOD) and selectivity, signal amplification strategies have been applied towards these sensors. In this perspective, we review recent advances in electrochemical biosensor signal amplification strategies for infectious disease diagnostics, specifically biosensors for nucleic acids and pathogenic microbes. We classify these strategies into target-based amplification and signal-based amplification. Target-based amplification strategies improve the LOD by increasing the number of detectable analytes, while signal-based amplification strategies increase the detectable signal by modifying the transducer system and keep the number of targets static. Finally, we argue that signal amplification strategies should be designed with application location and disease target in mind, and that the resources required to produce and operate the sensor should reflect its proposed application, especially when the platform is designed to be utilized in low-resource settings. We anticipate that, based on current technologies to diagnose infectious diseases, incorporating signal-based amplification strategies will enable electrochemical POC devices to be deployed for illnesses in a wide variety of settings.